The Leech Nervous System: A Valuable Model to Study the Microglia Involvement in Regenerative Processes - Françoise Le Marrec-Croq; Francesco Drago; Jacopo Vizioli; Pierre-Eric Sautière; Christophe Lefebvre (Clinical and Developmental Immunology)
Microglia are intrinsic components of the central nervous system (CNS). During pathologies in mammals, inflammatory processes implicate the resident microglia and the infiltration of blood cells including macrophages. Functions of microglia appear to be complex as they exhibit both neuroprotective and neurotoxic effects during neuropathological conditions in vivo and in vitro. The medicinal leech Hirudo medicinalis is a well-known model in neurobiology due to its ability to naturally repair its CNS following injury. Considering the low infiltration of blood cells in this process, the leech CNS is studied to specify the activation mechanisms of only resident microglial cells. The microglia recruitment is known to be essential for the usual sprouting of injured axons and does not require any other glial cells. The present review will describe the questions which are addressed to understand the nerve repair. They will discuss the implication of leech factors in the microglial accumulation, the identification of nerve cells producing these molecules, and the study of different microglial subsets. Those questions aim to better understand the mechanisms of microglial cell recruitment and their crosstalk with damaged neurons. The study of this dialog is necessary to elucidate the balance of the inflammation leading to the leech CNS repair.